Polymer sailing on rafts within lipid membranes - Jie Gao; Yiyang Shen; Shigeyuki Komura; Wenbing Hu; Lei Shen; Jinglei Hu (Proceedings of the National Academy of Sciences, 2025)
Understanding the dynamics of macromolecules adsorbed from extracellular fluids onto cell membranes is crucial for elucidating basic cellular processes and advancing applications in biotechnology, such as biosensing, therapeutics, and synthetic biology. However, this is complicated by the interplay between membrane heterogeneity, macromolecule conformation, and fluid hydrodynamics. We investigate the dynamics of linear polymers on binary lipid membranes using hydrodynamics simulations and single-molecule tracking experiments. We find that the preferential adsorption of nanosized polymer onto the raft-forming component of the membrane induces and stabilizes a single lipid raft that colocalizes with the polymer. This lipid raft, in turn, imposes dynamic confinement on the polymer, resulting in swollen yet restricted 2D conformations and Saffman–Delbrück-type diffusivity. These effects lead to an unusual scaling for polymer interfacial diffusion, D ∼ N − ν D with ν D ≈ 0.5 . Normal mode analysis further reveals that the relaxation time of the polymer’s slowest mode surprisingly follows the prediction of Zimm model for a 3D chain in a good solvent, irrespective of whether the polymer’s hydrodynamics are dominated by the 3D solvent or 2D fluid membrane. We also identify two diffusive modes: Saffman–Delbrück-type for polymer on heterogeneous membranes and Stokes–Einstein-like for polymer on homogeneous membranes, demonstrating the potential of polymer adsorbates as biosensors for membrane heterogeneity. Our study provides insights into polymer dynamics on biological membranes and suggests that polymer adsorbates can modulate lipid rafts, influencing raft-related cellular processes.